Epitaxial growth of higher transition-temperature VO2 films on AlN/Si - Tetiana Slusar; Jin-Cheol Cho; Bong-Jun Kim; Sun Jin Yun; Hyun-Tak Kim (APL Materials, 2016)
We report the epitaxial growth and the mechanism of a higher temperature insulator-to-metal-transition (IMT) of vanadium dioxide (VO2) thin films synthesized on aluminum nitride (AlN)/Si (111) substrates by a pulsed-laser-deposition method; the IMT temperature is TIMT ≈ 350 K. X-ray diffractometer and high resolution transmission electron microscope data show that the epitaxial relationship of VO2 and AlN is VO2 (010) ‖ AlN (0001) with VO2 [101] ‖